Experimental Study on Pedestal’s dynamic amplifying in UHV Electrical Equipment - LU Zhi-cheng; CUI Cheng-chen; ZHU Zhu-bing (Institute of Advanced Engineering and Science, 2012)
Simulation earthquake shaking table tests on the system of ultra high-voltage electrical equipment mounted on pedestals are carried out in order to study the dynamic amplifying effect of the pedestal in the system. The relationship between the dynamic responses of the system and main influence factors is studied by means of changing frequencies or stiffness and masses of the system under the driving function of several different earthquake waves. The studied results show that the dynamic amplifying effect of the pedestal in the system or the pedestal amplifying coefficient has close relationship with the stiffness and masses distributing or the frequencies of the system. Some regular and universal conclusions are obtained, and the suggested scale on the dynamic amplifying coefficient of the pedestal in the system is put forward, which provides reference for future design and engineering application on the ultra high-voltage electrical equipment with pedestal. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1647